Tekst . Tekst . Text . Текст - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program on books, music and poetry. Featured in the program: Kabakov, Aleksandr (Writer); Iskander, Fazil' Abdulovich (Writer); Artemov, Viacheslav (Composer); Naumov, Vladimir (Director); Zaitsev, Viacheslav (Fashion Designer) О книгах, поэзии, музыке, моде. В программе участвуют: Кабаков, Александр (Писатель); Искандер, Фазиль Абдулович (Писатель); Артемов, Вячеслав (Композитор); Наумов, Владимир (Режиссер); Зайцев, Вячеслав (Модельер)